Hak Anggota Serikat Pekerja Perspektif Hak Asasi Manusia - Nasution, Bahder Johan (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2015)
Abstract: The concept of rights and freedom as well as their guarantee cannot be separated from a system of value and principle that inspires them. In a democratic society, right and freedom are inherent in human, a guarantee of both, and their law enforcement, cannot be separated. The rights include rights to form a union and association. For workers this rights and freedom are implemented in the form of a labor union that serves as a means to make a political bargain with employers. The union is also important instrument for workers in fighting for their normative rights.Keywords: Trade union right, freedom of association.Â Abstrak: Konsep mengenai hak dan kebebasan maupun mengenai jaminannya tidak dapat dipisahkan dari sistem nilai dan asas yang mengilhaminya. Dalam suatu masyarakat demokratis, hak dan kebebasan yang melekat pada manusia, jaminan terhadap hak dan kebebasan itu, serta penegakannya secara hukum membentuk suatu kesatuan yang tidak dapat dipisahkan. Bagi pekerja hak dan kebebasan ini diimplementasikan dalam bentuk serikat pekerja yang berfungsi sebagai sarana untuk melakukan tawar menawar dengan pengusaha dan sebagai instrument dalam memperjuangkan hak-hak normatifnya.Kata Kunci: Hak serikat pekerja, kebebasan berserikat